2014
DOI: 10.1016/j.cub.2014.07.063
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Pacemaker Neurons Change Synaptic Contacts across the Day

Abstract: Summary Daily cycles of rest and activity are a common example of circadian control of physiology. In Drosophila rhythmic locomotor cycles rely on the activity of 150-200 neurons grouped in seven clusters [1, 2]. Work from many laboratories points to the small Lateral Neurons ventral (sLNvs) as essential for circadian control of locomotor rhythmicity [3-7]. sLNv neurons undergo circadian remodeling of their axonal projections opening the possibility for a circadian control of connectivity of these relevant cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
116
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(130 citation statements)
references
References 45 publications
9
116
3
Order By: Relevance
“…We found that VRI oscillations were similar to control flies in s-LNvs and DN1s (Figure S5E and data not shown), but had slightly altered rhythms in LNds (Figure S5E), whose connectivity with s-LNvs is rhythmic (Gorostiza et al, 2014). Thus s-LNv plasticity is required for optimal signaling with downstream neurons.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…We found that VRI oscillations were similar to control flies in s-LNvs and DN1s (Figure S5E and data not shown), but had slightly altered rhythms in LNds (Figure S5E), whose connectivity with s-LNvs is rhythmic (Gorostiza et al, 2014). Thus s-LNv plasticity is required for optimal signaling with downstream neurons.…”
Section: Resultsmentioning
confidence: 67%
“…(Gorostiza et al, 2014) recently showed that rhythms in s-LNv projection morphology are accompanied by rhythms in the number of pre-synaptic active zones. We used a fluorescently-tagged Bruchpilot-short (BRP short-strawberry ) transgene to detect active zones and confirmed that s-LNv projections have more BRP puncta at ZT2* than ZT14* (Figure 7A and S6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dendrite length also is circadianly regulated in the optic lobe with larger dendritic trees observed early in the (subjective) day (Weber et al 2009;Damulewicz and Pyza 2011). Notably for the regulation of output processes, the small ventral lateral circadian pacemaker neurons of Drosophila form differential synaptic contacts dependent upon the time of day (Fernández et al 2008;Gorostiza et al 2014). Rhythmic axonal remodeling occurs through matrix metalloproteinase regulation of the circadian neurotransmitter PDF , presumably due to the circadian regulation of matrix metalloproteinases (Kadener et al 2007;Nagoshi et al 2010).…”
Section: Mechanisms Linking the Circadian Clock And Memorymentioning
confidence: 99%